Production and Characterization of Edible Film from A Mixture of Tapioca Flour, Yellow Pump (Cucurbita moschatal D), Chitosan, and Glycerine for Application as A Layer Cake Packing. - Zaidar, Emma (Journal of Chemical Natural Resources, 2020)
The experiment of production and characterization of an edible film by mixing tapioca starch, pumpkin (Curcubita moschatal D.), chitosan, and glycerine with applications as the wrapping of layer cake has been done. The edible film was produced by mixing 2.5 g of tapioca starch, 3.5 g of pumpkin, and 40 mL of aquadest, then adding 4 % of chitosan, and 2 mL of glycerine. After homogenous, it was poured into an acrylic pan and dried in an oven at 35-45Â°C degrees for 2 days. Characterization of an edible film physically obtained thickness was 0.25 mm, tensile strength was 0.06 kgF/mm2 and elongation was 22.77 %. Morphology test of SEM (Scanning Electron Microscopy) produces edible film have pores that were tight, flat, and a bit compatible surface. And the FT-IR spectrum analysis showed the spectrum at 2939.52 cm-1 for the Alkana group (CH) and 3402.43 cm-1 for the hydroxyl group (OH). The result of the nutrition analysis of edible film was 28.2 % of carbohydrate content, 8.23 % protein content, 1.49 % of fat content, 25.6 % of water content, and 0.36% of ash content. An edible film can also be used as a wrapping for a layer cake.